Graphic Depictions: Portrayals of Mental Illness in Video Games. Issue 6 (26th October 2016) - Shapiro, Samuel; Rotter, Merrill
Abstract: Although studies have examined portrayals of mental illness in the mass media, little attention has been paid to such portrayals in video games. In this descriptive study, the fifty highest‐selling video games in each year from 2011 to 2013 were surveyed through application of search terms to the Wikia search engine, with subsequent review of relevant footage on YouTube. Depiction categories were then assigned based on the extent of portrayal and qualitative characteristics compared against mental illness stereotypes in cinema. Twenty‐three of the 96 surveyed games depicted at least one character with mental illness. Forty‐two characters were identified as portraying mental illness, with most characters classified under a "homicidal maniac" stereotype, although many characters did not clearly reflect cinema stereotypes and were subcategorized based on the shared traits. Video games contain frequent and varied portrayals of mental illness, with depictions most commonly linking mental illness to dangerous and violent behaviors.